A New Role of Vemurafenib as a Neoadjuvant Treatment of Axillary and Brain Melanoma Metastases. (23rd December 2013) - Melnik, Idit; Lotem, Michal; Yoffe, Boris
Abstract : Vemurafenib is approved by the FDA for the management of unresectable or metastatic melanoma. However, its role as a neoadjuvant therapy has not been determined. We present the first documented case in which vemurafenib induced complete tumor necrosis of both lymph node and brain metastases within one month or less, an outcome that indicated that the patient was a good candidate for excisional surgery.